Some Estimates of Rough Bilinear Fractional Integral - Yun Fan; Guilian Gao (Journal of Function Spaces and Applications)
We study the boundedness of rough bilinear fractional integral BΩ,α on Morrey spaces Lp,λ(ℝn) and modified Morrey spaces L~p,λ(ℝn) and obtain some sufficient and necessary conditions on the parameters. Furthermore, we consider the boundedness of BΩ,α on generalized central Morrey space B˙p,φ(ℝn). These extend some known results.